Ring-opening polymerization of a strained [3]nickelocenophane: a route to polynickelocenes, a class of S = 1 metallopolymers. - Baljak, S; Russell, A; Binding, S; Haddow, M; O'Hare, D; Manners, I (American Chemical Society, 2014)
We report the synthesis, reactivity studies, and ring-opening polymerization of a tricarba[3]nickelocenophane. The resulting green polynickelocene (5) possesses a -(CH2)3- spacer between the nickelocene units and is shown to be of high molecular weight. SQUID magnetometry measurements indicate that 5 is a macromolecular material with an S = 1 repeat unit.